Is the introduction of violence and injury observatories associated with a reduction of violence in adult populations? Rationale and protocol for a systematic review. Issue 7 (21st July 2015) - Jabar, Ardil; Barth, Dylan; Matzopoulos, Richard; Engel, Mark Emmanuel
Abstract : Introduction: The violence and injury observatories developed in Colombia and found throughout the Americas and Western Europe aim to maximise inter-institutional cooperation, information-sharing, analysis and security policy development initiatives to enhance governance. The purpose of the violence and injury observatories is directed towards preventing crime and violence at the local and regional levels. To date, there has been no systematic review of the literature to present a succinct review of the evidence. We therefore sought to summarise the evidence from existing studies on the contribution of violence and injury observatories towards violence prevention. Methods and analysis: A number of databases will be searched, supplemented by the same keyword searches in the grey literature. Search terms will include studies published from 1 January 1990 to 30 October 2014. Study quality will be assessed using a validated quality assessment tool. Two researchers will independently assess articles for study eligibility to reduce bias, minimise errors and enhance the reliability of findings. Disagreements will be resolved by consensus among three authors. This review protocol has been published in the PROSPERO International Prospective Register of systematic reviews, registration number 2014:CRD42014009818. Dissemination: There is a paucity of evidence for the effectiveness of violence and injury observatories and their influence on violence in an adult population. We plan to address this gap in knowledge by way of a systematic review and meta-analysis outlined in this abstract. We anticipate that the results could be used by researchers and policymakers to help inform them of the efficacy of violence and injury observatories and their broader role in contributing to violence prevention. Trial registration number: CRD42014009818.